Urban planning in Turkey as a process of translation - EKİN ERKAN, NİHAL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
There are several ways to define urban planning and to describe the diffusion of modern urban planning throughout the world. This article proposes a further way of describing this phenomenon by discussing the development of modern urban planning in Turkey as a process of translation. Modernization in Turkey has been experienced as a process of transfer of Western European models, in which interlingual translation too has served as a tool. However, the concept of translation is used here not only due to the existence of acts of translating within this process: the conception of translation as an intricate process involving difference and transformation, as proposed by contemporary translation studies, is a valuable analytical tool to analyze the transfer of urban planning more generally into the Ottoman and Turkish context. This paper thus uses a translation studies perspective to examine some of the agents and texts that helped form the field of modern urban planning in Turkey in the second half of the nineteenth century.
Keywords: urban planning and translation; urban planning in Turkey; Turkish modernity; cultural translation; Helmuth von Moltke; Ahmet Vefik Pasha